Cerebrospinal fluid examination may be useful in diagnosing neurosyphilis in asymptomatic HIV+ patients with syphilis - Salamano, Ronald; Ballesté, Raquel; Perna, Abayubá; Rodriguez, Natalia; Lombardo, Diego; García, Natalia; López, Pablo; Cappuccio, Pablo (Arquivos de Neuro-Psiquiatria, 2016)
Lumbar puncture in neurologically asymptomatic HIV+ patients is still under debate. There are different criteria for detecting neurosyphilis through cerebrospinal fluid (CSF), especially in cases that are negative through the Venereal Disease Research Laboratory (VDRL), regarding cellularity and protein content. However, a diagnosis of neurosyphilis can still exist despite negative VDRL. Treponema pallidum hemagglutination assay (TPHA) titers and application of the TPHA index in albumin and IgG improve the sensitivity, with a high degree of specificity. Thirty-two patients were selected for this study. VDRL was positive in five of them. The number of diagnoses reached 14 when the other techniques were added. It was not determined whether cellularity and increased protein levels were auxiliary tools in the diagnosis. According to our investigation, CSF analysis using the abovementioned techniques may be useful in diagnosing neurosyphilis in these patients.
Keywords: neurosyphilis; HIV positive; VDRL; TPHA in CSF; TPHA indexes